Evaluation of weeds as possible hosts of the potyviruses associated with tree tomato (solanum betaceum cav.) viroses (2012)
To determine possible weed hosts of potyviruses associated with the disease known as “tree tomato virus disease” in Antioquia department (Colombia), a sampling was conducted to identify weed species commonly found in commercial crops of S. betaceum affected by the virus and the possible presence of the virus in these plants. The encountered weed species were grouped into seven different taxonomic families, within which we evaluated the ten most common species. The selected weeds, three indicator species of the virus and tree tomato plants were grown in a greenhouse and mechanically inoculated with an extract of infected tree tomato tissue. One month after inoculation, the tree tomato plants and Nicotiana tabacum showed symptoms of the disease and were serologically positive, whereas none of the weeds showed symptoms or were positive for potyviruses serology. In order to confirm that the detection of the virus was not caused by low viral titers that did not reach the minimum detection level of the test used, the tomato tree plants were reinoculated with an extract of sap from the studied weeds and potyviruses was not detected in any of the tested weeds and therefore cannot be considered, with the utilized methodology, as hosts for the potyviruses affecting tree tomato plants.